Perceived group discrimination among Polish migrants to Western Europe: Comparing Germany, the Netherlands, the UK and Ireland - Frances McGinnity; Merove Gijsbertsa (The Economic and Social Research Institute (ESRI), 2015)
Discrimination is a problem for both minority groups and the societies in which they live. Perceived group discrimination reflects the direct experiences of immigrants but is also an indicator of the wider societal context and its level of social cohesion. This paper draws on new longitudinal survey data to examine perceptions of group discrimination among new Polish immigrants to four Western European countries (Ireland, the UK, the Netherlands and Germany). Are there cross-national differences in perceived group discrimination, and how is discrimination related to exposure to, and experiences in, the host country? Perceived discrimination is found to be higher among Polish migrants in the Netherlands in Wave 1 (2011) than in the other three countries; perceptions of discrimination also increased more there between waves of the survey, as well as in the UK. Perceptions of group discrimination are related to some aspects of exposure to the host country (e.g. duration in the country), but are most strongly associated with negative experiences in the host country. Differences in country contexts - attitudinal climate and national discourses - seem to play a strong role in understanding perceived group discrimination among new Polish immigrants in Western Europe.
Keywords: 330; Discrimination; Poles; new immigrants; integration; the United Kingdom; Germany; Ireland; the Netherlands; panel data